2022
DOI: 10.1227/neu.0000000000001966
|View full text |Cite
|
Sign up to set email alerts
|

Awake Mapping With Transopercular Approach in Right Insular–Centered Low-Grade Gliomas Improves Neurological Outcomes and Return to Work

Abstract: BACKGROUND:Asleep vs awake surgery for right insula–centered low-grade glioma (LGG) is still debated.OBJECTIVE:To compare neurological outcomes and return to work after resection for right insular/paralimbic LGG performed without vs with awake mapping.METHODS:A personal surgical experience of right insula–centered LGG was analyzed, by comparing 2 consecutive periods. In the first period (group 1), patients underwent asleep surgery with motor mapping. In the second period (group 2), patients underwent intraoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…The surgical resection of insular lesions is a challenge and is associated with a significant functional deficit ( 39 ). Two common open surgical options for insular lesions are the trans-sylvian and transcortical approaches with awake brain mapping ( 40 42 ). A meta-analysis of eighth studies evaluating 227 patients with insular gliomas showed that permanent neurological deficit was lower in cases with awake mapping (3.5 vs. 15.7%, p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The surgical resection of insular lesions is a challenge and is associated with a significant functional deficit ( 39 ). Two common open surgical options for insular lesions are the trans-sylvian and transcortical approaches with awake brain mapping ( 40 42 ). A meta-analysis of eighth studies evaluating 227 patients with insular gliomas showed that permanent neurological deficit was lower in cases with awake mapping (3.5 vs. 15.7%, p = 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the postoperative outcomes of LGG patients who benefited from intrasurgical multi-tasking in clinical routine, beyond an increase of the overall survival thanks to an optimization of the extent of resection ( 1 , 2 , 7 ), and besides the fact that the risk of long-term severe permanent neurological deficit is currently less than 1% ( 3 , 4 , 58 ), recent series in which objective neuropsychological assessments have systematically been performed after surgical resection demonstrated that a preservation or even an improvement of cognitive scores was found in most patients and should be considered as a standard of care – in patients with preoperative symptoms as well as in patients with incidental discovery of LGG ( 4 , 59 ). Interestingly, sparing the interplay between networks during a first surgery opened the door to subsequent operation(s) owing to mechanisms of functional reshaping which occurred in the meantime ( 2 , 60 , 61 ), and resulted in the maximization of resection while maintaining neurocognition and therefore quality of life ( 62 ).…”
Section: Practical Implications Of This Novel Intraoperative Mapping ...mentioning
confidence: 99%
“…Interestingly, sparing the interplay between networks during a first surgery opened the door to subsequent operation(s) owing to mechanisms of functional reshaping which occurred in the meantime ( 2 , 60 , 61 ), and resulted in the maximization of resection while maintaining neurocognition and therefore quality of life ( 62 ). Above all, the use of multi-tasking with time constraint in awake patient is associated with a higher rate of employment resumption ( 31 ), between 94% to 97% in recent experiences ( 3 , 4 , 58 ).…”
Section: Practical Implications Of This Novel Intraoperative Mapping ...mentioning
confidence: 99%
“…should also be pre-planned before the operation, in order for the patient and his or her family to organize appropriately in advance (in particular, arranging to stop work for a few weeks). This patient-specific surgical approach has led to minimization of severe permanent deficits (less than 1% occurrence), preservation or even improvement of postoperative cognitive scores, with RTW in over 94% of LGG patients [ 4 , 90 , 91 , 144 ]. Notably, RTW is a critical endpoint which has been severely neglected in the literature, and must be evaluated more systematically in future studies [ 145 ].…”
Section: Predicting Neural Interindividual Variability and Its Change...mentioning
confidence: 99%